(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article, which consists of a literature review, analyzes the results of studies presented in scientific articles and literature published over the past five years aimed at improving the occupational health of healthcare workers, and draws conclusions. The article examines factors related to emotional fatigue, stress, and the health of healthcare workers. To determine the level of healthy lifestyles among the population and morbidity rates, behavioral assessment criteria were studied. The level of adherence to healthy lifestyles among healthcare workers employed in healthcare institutions was studied, and a healthy lifestyle campaign was conducted among them. Maintaining a healthy lifestyle is important for physical and mental health and ensuring work efficiency, but the high workload of healthcare workers, night shifts, poor nutrition, and lack of physical activity have led to serious health problems. A number of studies conducted by scientists have proven that an unhealthy lifestyle leads to excess weight, emotional stress, and a reduced quality of life. The above data indicate the need to create conditions for regular adherence to the rules of a healthy lifestyle in the workplace in order to maintain the health and improve the efficiency of healthcare workers.